THE MARKETING OF RELIGIOUS PRODUCT TERAS DAKWAH: YOUTH PEOPLE AND THE POPULAR DAKWAH MOVEMENT - Romadi, Pipir; Irham, Muhammad; Saputra, Eko (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2022)
The da'wah movement in the contemporary era undergoes dynamic and development according to its social context. In this matter, the da'wah movement carried out by the certain community, has several strategies in developing efforts to attract followers and the mass to come in their community. This study endovour to highlight the popular da'wah movement framed by the marketing activities of religious product as its da'wah strategy. Specifically, this study explores the Yogyakarta  Teras Da’wah, which initiates the expansion of da'wah through several product marketing strategies, from various merchandise and marketed products. This research is important to see how youth people develop the da'wah movement through the marketing of religious product. This research used ethnographic study and field observations, to see and follow the da'wah activities of Da'wah Teras directly, and is strengthened by several interview with the administrators and congregations of Teras Da'wah. The result of this study indicated that Teras Da'wah uses the da'wah model as well as doing business as the da'wah movement. They market and sell religious products through recitation and non-recitation, such as traveling, camping, adventure, workshop, training, and futsal in collaborated with youth culture. Da'wah activities through the marketing of religious product include piety, community, lifestyle, identity and enjoyment.